Utilization of Museums and Cultural Heritage Sites in Pontianak As a Source for Learning Indonesian History - Mohammad Rikaz Prabowo; Supardi (Criksetra: Jurnal Pendidikan Sejarah, 2022)
Historical learning will be more meaningful if learners by doing education in the museum. The problem of this research is how to use museums and cultural reserves in Pontianak. The purpose of this study is to describe the use of museums and cultural reserves and their suitability in materials in historical subjects. The method used is qualitative descriptive through literature studies related to the chosen topic. The results of the research are first, the museum can add insight into the knowledge and journey of the nation, the love of the homeland, and the patriotism of learners. Musuem and cultural heritage as alternative learning resources, offsetting the limitations of learning in the classroom. Both can open the horizons of learners to see and live life and historical relics in the past for real. Second, budata museums and reserves in Pontianak that can be used as sources of historical learning include the West Kalimantan Provincial Museum and the Kadriyah Palace of the Pontianak Sultanate. Third, in the Provincial Museum there is a collection of geology, archaeology, history, and historical objects produced by pre-script culture until the islamic period. It is supportive as a source of historical learning and correlates with matter. While the Kadriyah Palace its existence can deepen the scientific treasures of learners about the material during the Islamic sultanates in Kalimantan.